15-Deoxy-Delta-12,14-prostaglandin J2 modulates pro-labour and pro-inflammatory responses in human myocytes, vaginal and amnion epithelial cells - Rasheed, Zahirrah BM.; Lee, Yun S.; Kim, Sung H.; Teoh, Tg; MacIntyre, David A.; Bennett, Phillip R.; Sykes, Lynne (Frontiers in Endocrinology, 2022)
Background: Prematurity is the leading cause of childhood death under the age of five. The aetiology of preterm birth is multifactorial; however, inflammation and infection are the most common causal factors, supporting a potential role for immunomodulation as a therapeutic strategy. 15-Deoxy-Delta-12,14-prostaglandin J2 (15dPGJ2) is an anti-inflammatory prostaglandin and has been shown to delay lipopolysaccharide (LPS) induced preterm labour in mice and improve pup survival. This study explores the immunomodulatory effect of 15dPGJ2 on the transcription factors NF-κB and AP-1, pro-inflammatory cytokines, and contraction associated proteins in human cultured myocytes, vaginal epithelial cell line (VECs) and primary amnion epithelial cells (AECs). Methods: Cells were pre-incubated with 32µM of 15dPGJ2 and stimulated with 1ng/mL of IL-1β as an in vitro model of inflammation. Western immunoblotting was used to detect phosphorylated p-65 and phosphorylated c-Jun as markers of NF-κB and AP-1 activation, respectively. mRNA expression of the pro-inflammatory cytokines IL-6, IL-8, and TNF-α was examined, and protein expression of COX-2 and PGE2 were detected by western immunoblotting and ELISA respectively. Myometrial contractility was examined ex-vivo using the DMT myograph. Results: 15dPGJ2 inhibited IL-1β-induced activation of NF-κB and AP-1, and expression of IL-6, IL-8, TNF-α, COX-2 and PGE2 in myocytes, with no effect on myometrial contractility or cytotoxicity. Despite inhibiting IL-1β-induced activation of NF-κB, expression of IL-6, TNF-α, and COX-2, 15dPGJ2 led to activation of AP-1, increased production of PGE2 and increased cell death in VECs and AECs. Conclusion: We conclude that 15dPGJ2 has differential effects on inflammatory modulation depending on cell type and is therefore unlikely to be a useful therapeutic agent for the prevention of preterm birth.